PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASTRA UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Wahyu Try Andaru; Irma Arifah (Jurnal Komposisi, 2021)
This study aims to develop animation-based animastra learning media for folk poetry material for grade VII students and determine the feasibility of animation-based animastra learning media based on the assessment of media experts, material experts and student responses. This type of research is Research and Development (R&D) with potential and problem steps, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, and final products. The research development model used is ADDIE, with the stages of analysis, design, development, implementation and evaluation. The population of this study were students of SMPN 4 Pagerwojo class VII with a total of 20 students. The sample is all students from the existing population. Data collection techniques used are interviews and questionnaires. The results show that animation-based animastra learning media is feasible to use with a percentage of 97% of media expert validation questionnaires and 82% of material experts and 87% of student response questionnaire percentages in the very good category. The conclusion in this study is that animation-based animastra learning media is feasible, effective and efficient to use and attracts students' interest in learning. Further researchers is suggested to use research results as input and innovation to create interesting unique learning media so that those students do not get bored is learning.